A Study to Evaluate Prognostic Factors and Define a Critical Volume for Early Surgery in Patients with Bifrontal Brain Contusions - Kumari M, Manoranjitha; Senthilkumar, T.P. Jeyaselva; Ravi, Yamunadevi (Indian Journal of Neurosurgery, 2023)
Aim The aim of this study was to evaluate various prognostic factors and their impact on the outcome of patients with bifrontal brain contusions and to define the critical volume of bifrontal brain contusions and to advice early surgeryMaterials and Methods This is a prospective study performed with 250 patients admitted in a tertiary care hospital in Chennai.Observations and Results In this study, we have studied the various findings in computed tomography (CT) scan brain that haves influence over the outcome. These are: Bilateral squashing of frontal horn, Posterior shift of genu, The deformation of third ventricle, The complete obliteration of basal cisterns, 5. Development of delayed intracranial hemorrhage (ICH). All these factors are associated with worst outcome and in patients those developed delayed increase in contusion volume, the median volume of contusion at the admission time ranged from 22 to 32 mL and the mean being 27 mL, we recommend prophylactic surgery in this subset of patients to prevent them from developing rapid deterioration in Glasgow coma scale (GCS) due to delayed ICH.Conclusion Critical volume of bilateral frontal contusion that warrants prophylactic surgical intervention irrespective of the admission GCS is 27 mL. Younger age and good admission GCS are independent predictors for better outcome. Patients with volume of contusion more than 50 mL are always associated with unfavorable outcome. Bilateral frontal horn squashing, anteroposterior shift of genu of corpus callosum, deformation of third ventricle, and obliteration of basal cisterns are CT predictors for poor outcome in bifrontal brain contusions.
Keywords: bifrontal contusions; early surgery; frontal contusions